1236. Safety and Immunogenicity of a 20-Valent Pneumococcal Conjugate Vaccine (PCV20) in Healthy Infants in the United States. (31st December 2020) - Senders, Shelly; Klein, Nicola P; Lamberth, Erik; Thompson, Allison; Drozd, Jelena; Trammel, James; Peng, Yahong; Giardina, Peter; Jansen, Kathrin U; Gruber, William C; Scott, Daniel; Watson, Wendy
Abstract: Background: A 20-valent pneumococcal conjugate vaccine (PCV20) is being developed to extend protection against pneumococcal disease beyond that of the 13-valent pneumococcal vaccine (PCV13). This is the first safety and immunogenicity study of PCV20 in healthy infants. Methods: This randomized, double-blind study enrolled and randomized (1:1) healthy infants ≥ 42 to ≤ 98 days of age to receive a 4-dose series of either PCV20 or PCV13 (control) at 2, 4, 6, and 12 months of age. Local reactions and systemic events were assessed for 7 days after each vaccination; adverse events (AEs) and serious AEs (SAEs) were collected throughout the study. PCV20 immune responses (serotype-specific immunoglobulin G [IgG] and opsonophagocytic activity [OPA]) were measured in sera 1 month after the third infant dose and the fourth dose at 12 months of age. Results: There were 460 subjects enrolled, with 416 and 391 subjects receiving 3 and 4 doses, respectively. Local reactions and systemic events were predominantly mild to moderate in severity and similar among vaccine groups. There were no related SAEs or deaths reported. PCV20 elicited IgG responses 1 month after the third dose with boosting after a fourth dose. OPA responses were also observed. Conclusion: PCV20 was well tolerated with a safety profile similar to PCV13. PCV20 elicited immune responses to all 20 vaccine serotypes. Disclosures: Shelly Senders, MD, Pfizer (Grant/Research Support) Nicola P. Klein, MD, PhD, GSK group of companies (Research Grant or Support)Merck (Grant/Research Support)Pfizer (Grant/Research Support)Protein Science (now SP ) (Grant/Research Support)Sanofi Pasteur (Grant/Research Support) Erik Lamberth, MD, Pfizer (Employee) Allison Thompson, MD, Pfizer (Employee) Jelena Drozd, MS, Pfizer (Employee) James Trammel, MS, Pfizer (Employee) Yahong Peng, PhD, Pfizer (Employee, Shareholder) Peter Giardina, PhD, Pfizer (Employee) Kathrin U. Jansen, PhD, Pfizer (Employee, Shareholder) William C. Gruber, MD, Pfizer (Employee, Shareholder) Daniel Scott, MD, Pfizer (Employee, Shareholder) Wendy Watson, MD, Pfizer (Employee, Shareholder)